2013
DOI: 10.1007/s11051-013-1428-5
|View full text |Cite
|
Sign up to set email alerts
|

Fulvic acids concentration and pH influence on the stability of hematite nanoparticles in aquatic systems

Abstract: In aquatic systems, fulvic acids (FAs) are expected to play key roles on the stability and aggregation behavior of manufactured nanoparticles (NPs). The exact conditions under which aggregation or dispersion occurs will depend on the nanoparticle surface charge properties, FAs concentration as well as solution conditions, such as pH and ionic strength. The systematic calculation of stability (aggregation versus disaggregation) diagrams is therefore a key aspect in the prediction of the environmental fate and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Z-average diameter variations were found different starting from different pH due to the formation of large aggregates when the PZC region was reached. As shown by Palomino and Stoll (2013), the zeta potential was not found to exhibit hysteresis by increasing or decreasing the pH values. This indicates that the hematite charging process is not dependent on the aggregate formation.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Z-average diameter variations were found different starting from different pH due to the formation of large aggregates when the PZC region was reached. As shown by Palomino and Stoll (2013), the zeta potential was not found to exhibit hysteresis by increasing or decreasing the pH values. This indicates that the hematite charging process is not dependent on the aggregate formation.…”
Section: Resultsmentioning
confidence: 81%
“…The NPs were stored as a 0.2 g/L suspension in a cold and dark environment. After image analysis of more than 50 SEM pictures by Palomino and Stoll (2013), the mean SEM diameter of the individual nanoparticles was found equal to 53 ± 5 nm confirming that the nanoparticle sizes were reasonably monodispersed. The Z-average hydrodynamic diameter was found equal to 94 ± 3 nm at pH = 3, indicating the presence of dimmers and trimers in solution.…”
Section: Hematite Synthesismentioning
confidence: 78%
See 2 more Smart Citations
“…This means that at this concentration the extent of disaggregation of the NP colloids in the presence of the concentration of humic substances is the highest. Palomino and Stoll [35] also found that very low concentrations of fulvic acids (0.1-5 mg/L) showed a similar effect on iron hydroxide NP solutions. Figure 4 provides a quantitative extent of disaggregation of the 12 NP colloids in the pure water and the algae medium when the humic substance is present at the concentration.…”
Section: Experimental Evaluation Of Humic Substances Impacts On Np Agmentioning
confidence: 79%